One-hour post-load glucose is associated with severity of hepatic fibrosis risk. (July 2022) - Jagannathan, Ram; Fiorentino, Teresa Vanessa; Marini, Maria Adelaide; Sesti, Giorgio; Bergman, Michael
Abstract: Aim: Individuals with high 1-hour post-load glucose (1-h PG > 155 mg/dl; 8.6 mmol/l) during an oral glucose tolerance test are at increased risk of type 2 diabetes (T2D) and cardiovascular complications, hepatic steatosis, and mortality. However,  the clinical relevance of 1-h PG for the severity of hepatic fibrosis risk remains undefined. Methods: Cross-sectional data of the CATAMERI study (n = 2335) were analyzed. Participants underwent anthropometric measurements, liver enzyme determinations, cardiometabolic profiling, and a 75-gram oral glucose tolerance test, including fasting, 1-h and 2-h PG determinations and measurement of FIB-4 score to assess degree of hepatic fibrosis. Multivariable logistic regression analysis was performed to evaluate risk of advanced hepatic fibrosis with worsening glycemic status. Results: We stratified the study group into 6 categories based on glycemic status: normal glucose tolerance (NGT) 1h-PG Low, NGT 1h-PG High, iIFG 1h-PG Low, iIFG 1h-PG High, IGT, and newly detected T2D. Anthropometric and cardiometabolic profiles worsened gradually with glycemic status. Moreover, compared to NGT-1h-PG Low group, worsening glycemic status was significantly associated with the severity of fibrosis, independent of other significant clinical risk factors. Conclusions: 1-PG is a valuable tool for stratifying subjects with NGT or IFG at heightened risk of hepatic fibrosis requiring further evaluation with elastography.